Evaluation of biochemical, histopathological, hematological, and genotoxic effects of some indigenous weed plant extracts in albino rats toward a natural and safe alternative to synthetic insecticides - Zahoor, Muhammad Asif; Zahoor, Muhammad Kashif; Rizvi, Hina; Nawaz, Zeeshan; Ahmed, Aftab; Munir, Bushra; Hassan, Mudassir; Zulhussnain, Muhammad (Frontiers in Veterinary Science, 2026)
IntroductionThe indiscriminate use of pesticides poses a significant risk to human health and the environment. Plant-based biopesticides offer an alternative to insecticides for integration into insect pest management programs.MethodsThe current study assessed the toxicological effects of leaf extracts from indigenous weed plants, Chenopodium murale and Achyranthes aspera, in albino rats, Rattus norvegicus. The extract-mixed diet was fed in three different doses (100 ppm, 150 ppm, and 250 ppm) for 28 days, while the Cypermethrin insecticide was used as a reference insecticide at the same dose levels. Samples from liver and kidney tissues were collected for histopathological study, and the blood serum was obtained for biochemical assay.Results and discussionHistopathological analysis of cypermethrin revealed congestion in the central vein, hemorrhage in hepatic tissues, and necrosis of liver tissues, while kidney tissues showed necrosis of renal tubules, fibrosis, and swelling in Bowman’s capsule. Moreover, hemorrhage was attenuated by degenerated inflammatory cells, edema, and shrinkage, and the rupturing of glomeruli was also observed. Mortality was also recorded at 28th day. In contrast, no physical signs of toxicity and significant alteration in liver and kidney tissues were shown by both plant extracts. Acetylcholinesterase (AChE) and phosphatase enzymes also showed non-significance with plant extracts and significant results with Cypermethrin. Similarly, genotoxicity through the comet assay revealed no changes for either plant. Hematological parameters showed no significant change with plant extracts. Non-significant results revealed that both plant extracts had no difference when compared to the control for all parameters, which indicates that the weed plants are less toxic as compared to Cypermethrin in vertebrates.ConclusionThese findings suggest that these weed plants have the potential to be used as biopesticides for future integrated pest management (IPM) programs.